Integrated Management of Seed borne Nematode (Aphelenchoides besseyi) in T. Aman Rice (Oryza sativa L.) (The Agriculturists, 2016)
Two experiments were conducted in the Nematology Laboratory of the Seed Pathology Centre and experimental field of the Department of Agronomy, Bangladesh Agricultural University (BAU), Mymensingh during 2004 to examine the influence of physical and chemical treatments on the seed borne nematode disease of rice. The integrated control with physical and chemical treatments against seed borne nematode (Aphelenchoides besseyi) causing white tip disease of rice varieties BR11 and Nizersial (T. Aman) rice revealed that farmers saved seeds of both the varieties treated simultaneously with brine solution, hot water and Furadan 3G resulted in enhanced plant height, root length, panicle length, number of grains per panicle, total number of spikelets per panicle,  grain yield and lower association of seed borne nematode. Better responses were found with farmers saved seeds treated with brine solution and hot water than field application of Furadan  3G, hot water treatment and treatment with brine solution having higher plant growth characters and yield of grains correspondingly with lower number of sterile and discolored spikelets and seed borne nematode compared to the control.The Agriculturists 2015; 13(1) 79-86